Introduction (The Hadhrami Diaspora in Southeast Asia: Identity Maintenance or Assimilation?) - Abu Shouk, Ahmed Ibrahim; Ahmed Ibrahim, Hassan (E.J. Brill, 2009)
Based on papers presented at the international conference, held in Kuala Lumpur on August 26-28, 2005.